Role of Indonesia Women in K'tut Tantri's Revolt in Paradise novel (2006): a feminist approach - NOVIANA, ITA (2011)
The problem statement of this research is how role of Indonesian women is reflected in K'tut Tantri's Revolt in Paradise novel based on a feminist approach. This research is aimed to describe K'tut Tantri's Revolt in Paradise novel based on the structural element of the novel and to analyze role of Indonesian women in K'tut Tantri's Revolt in Paradise Novel (2006) based on feminist approach. In this research, the writer uses qualitative method. The object of this research is Revolt in Paradise Novel (2006). There are two types of the data and the data sources consist of primary and secondary data sources. The primary data source is Revolt in Paradise novel itself and secondary data sources are biography of the author and other relevant or reference related to this study. The results of this study based on the analysis, the writer concludes the first, K'tut Tantri wants to describe her role to gain Indonesia's independence so she can show to all of Indonesian woman that they have role to defend their country. The role of women and men are equally important in all aspects of life. All the people of Indonesia must struggle to get Independence. The second, the major character in this novel is also the narrator because this novel is autobiography of the writer herself.